Preliminary study of in vitro propagation of a selected high yielding clone of kacip fatimah (Labisia pumila VAR. alata) - Syafiqah Nabilah, S.B.; Farah Fazwa, M.A.; Nor Hasnida, H.; Siti Suhaila, A.R.; Norhayati, S.; Nazirah, A.; Muhammad Fuad, Y.; Haliza, I.; Mohamad, O. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Kacip Fatimah (Labisia pumila), an undershrub herb from the Myrsinaceae family, is traditionally used as medicine, particularly by Malay women during post-natal care. The development of L. pumila as a medicinal herb has led to its commercialization and increasing demand. To ensure its sustainable supply, the propagation of kacip Fatimah on a large scale such as through tissue culture needs to be explored. In this study, the leaves of a selected high yielding clone of kacip Fatimah, clone AA28, were used as explants. After surface sterilization, the explants were cultured on MS basal medium containing 0.5 mg/l NAA with different concentrations of BAP ranging from 0.05 to 0.15 mg/l for shoot induction. The explants cultured in MS medium containing 0.5 mg/l NAA in combination with 0.05 mg/l BAP produced the highest mean number of shoots per explants (10 ± 0.1). The shoot multiplication study is in progress and will be reported in a future paper.